IMPLEMENTATION OF UNDERWRITING RISK MANAGEMENT IN PT. ASURANSI JASINDO SYARIAH - Wahyu Rofikah; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study purpose to how the risk management process in PT Asuransi Jasindo Syariah with a case study of vehicle insurance class of business. This research uses a qualitative approach with a descriptive case study strategic. The research data was obtained through primary data in the form of interviews and secondary data. The selection of informants in interviews through snowball sampling techniques and secondary data obtained from supporting data in the form of archives, reports and relevant document and literature reviews related to research. The results of this study indicate that PT Asuransi Jasindo Syariah has a significant role in the process of underwriting risk management, especially in vehicle insurance product, which have the highest loss ratio among other products. The underwriting risk management process carried out by PT Asuransi Jasindo Syariah is risk identification, risk measurement, risk monitoring, and risk control.Keywords: risk management, underwriting, syariah insuranceREFFERENCE Ahmad, R dan Abdul H. (2008). Lembaga keuangan syariah. Jakarta: Zikrul Hakim.Ali, AM. (2004). Asuransi dalam perspektif hukum Islam. Jakarta: Prenada Kencana.Amrin, A. (2006). Asuransi syariah keberadaan dan kelebihan ditengan asuransi konvensional. Jakarta: PT Elex Media Komputindo.Burhanuddin. (2010). Aspek hukum lembaga keuangan syariah. Jakarta: Graha Ilmu.Darmawi, H. (2006). Manajemen risiko. Jakarta: Bumi Aksara.Dewi, G. (2007). Aspek-aspek hukum dalamperbankan dan perasuransian syariah di Indonesia. Jakarta: Kencana. Fatrisia, L. (2015). Tinjauan ekonomi Islam terhadap manajemen risiko penyaluranpinjaman bakulan pada PT. Permodalan Ekonomi Rakyat Provinsi Riau Pekanbaru. Skripsi tidak diterbitkan. Pekanbaru: Universitas Islam Negeri Sultan Syarif Kasim Riau.Huggins, K dan Robbert D. (1996). Operasi perusahaan asuransi jiwa dan asuransi kesehatan. Jakarta: Yayasan Dharma Bumiputera.Irnawati, I. (2011). Implementasi manajemenrisiko di PT. Bringin Life Syariah. Skripsi tidak diterbitkan. Jakarta: UIN Syarif Hidayatullah.Rahmawati, D. (2017). Implementasi underwriting pada penerbitan polis di AJB Bumiputera 1912 divisi syariah cabang Sidoarjo. Skripsi tidak diterbitkan. Surabaya: Universitas Islam Negeri Sunan Ampel SurabayaSalinan Peraturan Menteri KeuanganNo.18/PMK.010/2010 tentang Penerapan Prinsip Dasar Penyelenggaraan Usaha Asuransi dan Usaha Reasuransi dengan Prinsip Syariah. Jakarta: Menteri KeuanganSurat Edaran Otoritas Jasa Keuangan Nomor 6/SEOJK.05/2017 tentang Penetapan Tarif Premi atau Kontribusi pada lini Usaha Asuransi Harta Benda dan Asuransi Kendaraan Bermotor Tahun 2017Pemerintah Indonesia. (2014). Undang-Undang No. 40 Tahun 2014 tentang Asuransi. Lembaran Negara RI Tahun 2014 No. 40. Jakarta: Sekertariat NegaraPeraturan Otoritas Jasa Keuangan Nomor 1/POJK.05/2015 tentang Penerapan Manajemen Risiko Bagi Lembaga Keuangan Non-BankPolis Standar Asuransi Kendaraan Bermotor Indonesia 2018 – Asosiasi Asuransi Umum IndonesiaSalim, A. (2005). Asuransi dan manajemen risiko. Jakarta: PT. Raja Grafindo Persada.Saniatusilma, Hifi dan Suprayogi, Noven. (2015). Manajemen risiko dana tabarru’ pada PT. Asuransi Jiwa Syari’ah Al-Amin. Jurnal Ekonomi Syariah Teori dan Terapan, 2(12), 1002-1018.Sukmadinata. (2008). Metode penelitian kualitatif. Bandung: Graha Aksarandu.Sula, S. (2004). Asuransi syariah (life and general): Konsep dan sistem operasional.Jakarta: Gema Insani Press.Suseno, P. (2014). Konsep dasar manajemenrisiko. Tangerang: Universitas Terbuka.Susilo, L., dkk. (2018). Manajemen risiko berbasis ISO 31000 untuk industri nonperbankan. Jakarta: PPM Manajemen.Wahyudi, dkk. (2013). Manajemen risiko bank Islam. Jakarta: Salemba Empat.Yin, Robert K. (2008). Case study research: Design and methods (applied social research methods). Illinois: Sage Publications, Incwww.jasindosyariah.co.id